A novel impedimetric sensor for trace level detection of dimethyl sulfide (DMS) - Iden, Hassan; de Faria, Ricardo Adriano Dorledo; Heneine, Luiz Guilherme Dias; Matencio, Tulio; Messaddeq, Younès [UNESP] (Springer Nature, 2020)
An easy and effective method for the preparation of a new impedimetric sensor used in the detection of dimethyl sulfide (DMS) at a nanomolar level is presented. The sensor was prepared in two steps from a commercially available screen-printed carbon electrode (SPCE): a simple activation of the SCPE using cyclic voltammetry followed by electroless plating of the working electrode surface with gold clusters. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) techniques confirmed the successful functionalization of the SPCE, revealing the presence of gold particles dispersed on the carbon matrix. Electrochemical impedance spectroscopy (EIS) was used to study the sensitivity of the sensor towards DMS dissolved in aqueous solution and simulated ocean water. Analyses were performed in less than 3 min, and the sensor showed linearity in a concentration range from 1.0 × 10−10 to 1.0 × 10−8 M with a limit of detection of 1.50 × 10−9 M and a limit of quantification of 2.27 × 10−9 M. To simulate the marine environment in which DMS is naturally present in nature, the impedance of the sensor was monitored by online EIS. Moreover, results indicated that, despite not linearly, the sensor is a promising tool to detect the analyte even at 1.0 × 10−11 M, presenting an increase of resistance of 13.5% in relation to its bare condition.